Free at last - J. Pefanis (Law Text Culture, 1998)
I met the philosopher a few years ago when he was director of the College of Philosophy. (A significant detail that underlines his commitment to knowledge, education and the proposition that 'childhood is the season of the mind's possibilities.) To arrange our meeting- I wanted to discuss a matter oftranslation - I telephoned him.